Harry M. Miller and Robert Stigwood present ... Jesus Christ superstar. - Capitol Theatre (Sydney, N.S.W.) ([Sydney] : Capitol Theatre, 1972)
Poster promoting performances at the Capitol Theatre, Sydney. Features the musical's angel logo in gold, centred on a brown background. Lettering in white.
Caption title.
Also available online
National Library of Australia's copy is from the collection of Anne Young.
Born in New Zealand, Miller moved to Australia in 1963, where he established Pan Pacific Productions with Keith and Dennis Wong. During the 1960s, Pan Pacific promoted many concert and theatrical tours of Australia and New Zealand. During the late 1960s Miller and Kenn Brodziak of Aztec Services Ltd became colleagues and subsequently collaborated on many concert and theatrical promotions. In 1969, Miller discovered the American singer Marcia Hines in Boston, USA, while casting African-American performers for the Australian stage version of Hair. Miller went on to produce the acclaimed and highly successful Australian productions of Jesus Christ Superstar in 1972 and The Rocky Horror Show in 1974, both of which used many of the production staff from Hair.
Keywords: Miller, Harry M. -- 1934-2018.; Stigwood, Robert, -- 1934-2016.; Capitol Theatre (Sydney, N.S.W.) -- Posters; Jesus Christ superstar (Musical theater); Musical theater -- Australia -- Posters; Performing arts -- Australia -- Posters; Theaters -- Australia -- Posters